H3K27me3 demethylases alter HSP22 and HSP17.6C expression in response to recurring heat in Arabidopsis - Yamaguchi, Nobutoshi; Matsubara, Satoshi; Yoshimizu, Kaori; Seki, Motohide; Hamada, Kouta; Kamitani, Mari; Kurita, Yuko; Nomura, Yasuyuki; Nagashima, Kota; Inagaki, Soichi; Suzuki, Takamasa; Gan, Eng-Seng; et al. (Nature communications, 2021)
Acclimation to high temperature increases plants’ tolerance of subsequent lethal high temperatures. Although epigenetic regulation of plant gene expression is well studied, how plants maintain a memory of environmental changes over time remains unclear. Here, we show that JUMONJI (JMJ) proteins, demethylases involved in histone H3 lysine 27 trimethylation (H3K27me3), are necessary for Arabidopsis thaliana heat acclimation. Acclimation induces sustained H3K27me3 demethylation at HEAT SHOCK PROTEIN22 ( HSP22 ) and HSP17.6C loci by JMJs, poising the HSP genes for subsequent activation. Upon sensing heat after a 3-day interval, JMJs directly reactivate these HSP genes. Finally, jmj mutants fail to maintain heat memory under fluctuating field temperature conditions. Our findings of an epigenetic memory mechanism involving histone demethylases may have implications for environmental adaptation of field plants. Acclimation to high temperature increases tolerance of heat shock in plants. Here the authors show that JUMONJI H3K27me3 demethylases are needed for heat acclimation in Arabidopsis and act at loci encoding HEAT SHOCK PROTEINS to facilitate induction upon heat stress.